Pemberdayaan Santri Al-Rifa’ie Satu Melalui Ujian Kepesantrenan: Rekonstruksi Epistemologi Kepemimpinan Khidmah - Intan, Intan Karisma; Muhammad Husni (CV. KAMPUS AKADEMIK PUBLISING, 2026)
This community service program aims to empower final-year students (santri) at Al-Rifa’ie 1 Islamic Boarding School through the epistemological reconstruction of